Harmonic Current Injection Control Algorithm for Narrowing the Switching Frequency Range in CrM Totem-Pole PFC - Park, Hae-Chan; Ji, Min-Woo; Kim, Dong-Joong; Lee, Gi-Young; Kim, Rae-Young (IEEE transactions on power electronics, 2025)
Power factor correction (PFC) converters are utilized extensively across various applications, and therefore, developing customized control algorithms is essential to meet the diverse operational requirements. In critical conduction mode totem-pole PFC technology, introducing harmonic currents into a command signal is a viable approach for enhancing the performance of the PFC converter. However, this approach suffers from the risk of exceeding the planned harmonic current injection because of external interference. To overcome this issue, this article introduces a novel control algorithm that incorporates a harmonic injection technique to maintain stable performance despite disturbances or load variations. This algorithm uses Fourier analysis to precisely calculate each harmonic component and employs proportional-integral compensation along with feedforward corrections method to inject harmonic currents accurately in alignment with theoretical expectations. The efficacy of the proposed algorithm is validated through experiments conducted on a 350 W totem-pole PFC converter prototype under various load conditions. A comparison between the harmonic injection commands determined through a power analyzer and the actual measurements revealed that control was maintained within an error margin of 4.5%, demonstrating that harmonic control was effectively operational even under load variations.